2022
DOI: 10.3390/microorganisms10061134
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Comparison of Ca. Neoehrlichia mikurensis Genomes

Abstract: Ca. Neoehrlichia mikurensis is widely prevalent in I. ricinus across Europe and has been associated with human disease. However, diagnostic modalities are limited, and much is still unknown about its biology. Here, we present the first complete Ca. Neoehrlichia mikurensis genomes directly derived from wildlife reservoir host tissues, using both long- and short-read sequencing technologies. This pragmatic approach provides an alternative to obtaining sufficient material from clinical cases, a difficult task for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The prevalence of CNM in our vole community ranged 24–47% depending on Microtus species. This is a moderate rate of prevalence, similar values having been reported in at least seven papers for the most commonly studied rodent species in several countries in Europe 5 , 8 , 10 , 13 , 53 , 55 , 56 . In one study, much lower values (prevalence < 2%) were reported 7 and in two studies in Germany prevalence (> 55%) was found to be slightly higher compared to that in our work 9 , 12 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of CNM in our vole community ranged 24–47% depending on Microtus species. This is a moderate rate of prevalence, similar values having been reported in at least seven papers for the most commonly studied rodent species in several countries in Europe 5 , 8 , 10 , 13 , 53 , 55 , 56 . In one study, much lower values (prevalence < 2%) were reported 7 and in two studies in Germany prevalence (> 55%) was found to be slightly higher compared to that in our work 9 , 12 .…”
Section: Discussionsupporting
confidence: 86%
“…In one study, much lower values (prevalence < 2%) were reported 7 and in two studies in Germany prevalence (> 55%) was found to be slightly higher compared to that in our work 9 , 12 . Hence, there is a some disparity in prevalence values for the most commonly studied species, ranging 0.3–33% for A. agrarius 7 , 12 , 57 , 1.7–65% for A. flavicollis 5 , 7 10 , 12 , 13 , 53 , 56 , 57 , 1.1–58% for M. glareolus 5 , 7 10 , 12 , 13 , 53 , 55 – 57 , and 11–33% for A. sylvaticus 5 , 8 , 10 , 53 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…These genera include Anaplasma phagocytophilum and Ehrlichia chaffeensis that cause human granulocytic anaplasmosis and human monocytic ehrlichiosis, respectively and Ehrlichia ruminantium that causes heartwater (cowdriosis) in African cattle [ 1 , 11 , 12 , 18 , 33 ]. Recent advances in the genomics of these major pathogens have shed new light on the intracellular lifestyle of Anaplasmataceae and the mechanisms by which they induce and evade the innate immune response [ 2 , 15 , 17 , 25 ]. Current epidemiological surveys on Anaplasmataceae are now uncovering emergent tick-borne pathogens such as Neoehrlichia mikurensis , causing neoehrlichiosis in Europe and Asia [ 31 , 38 ], and Ca.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of paired-end reads (with a cumulative score of > 20.000 read pairs) were assigned to known tick borne pathogens: Anaplasma phagocytophilum was found to be present in tick Ir_d1 and Ir_d9, both collected from the dune area; Borrelia afzelii was found to be present in tick Ir_d9 and Neoehrlichia mikurensis [96] was present in tick Ir_f3 collected from the forested area. Rickettsiella species have been identified as facultative endosymbionts of I. ricinus ticks [97] and with more than 1 million read pairs assigned, Ricketssiella species appear to be present in Ir_d1, Ir_d6 and Ir_d7 (Figure 2).…”
Section: Deep Sequencing Of I Ricinus Adult Females Reveals the Prese...mentioning
confidence: 99%